PENGARUH FAKTOR KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN - JE, Erna Atiwi (Manajemen & Bisnis Jurnal, 2015)
Abstract.As an institution that is engaged in a self- service unit Cooperative " DAU " Malang should be able to improve the quality of care for the management of the business has to offer. In running a business unit of supermarket / retail managed by the Cooperative " DAU " Malang is not free from the problems that confronted the other supermarket / retail as competitors, such as alfamart and Indomaret. In order to face existing competition, self-service unit / retail managed by the Cooperative " DAU " Malang need to provide excellent service. The purpose of the study to determine the effect of simultaneous, partial and influence of the most dominant factor of quality of services consisting of physical evidence, reliability , responsiveness, assurance, and empathy towards customer satisfaction Cooperative supermarket unit " DAU " Malang. By using multiple regression analysis and concluded bahawa simultaneous partial service quality factors consist of physical evidence, reliability, responsiveness, assurance, and empathy affects customer satisfaction Cooperative supermarket unit " DAU " Malang, while assurance is the dominant variable affecting customer satisfaction. Based on these results, it is advisable for the Cooperative supermarket unit " DAU" Malang need to pay attention to hygiene conditions supermarket space. As for the employees, especially the salesperson needs to pay attention to accuracy in the recording of goods bought by consumers, immediately follow up when an error occurs, increase the knowledge about the ethics of service and always act fairly in providing services . Keywords : Quality of service and customer satisfaction